Clinical value of mean platelet volume/lymphocyte ratio and degree of coronary artery disease in patients with chronic kidney disease - Li Ying-bin; Li Sheng-kai (Linchuang shenzangbing zazhi)
ObjectiveTo investigate the relationship between mean platelet volume to lymphocyte ratio （MPVLR） and the degree of coronary artery disease in patients with chronic kidney disease （CKD） and its clinical significance.MethodsThe clinical data of 111 patients with chronic kidney disease diagnosed by coronary angiography in our affiliated hospital in recent 6 years were analyzed retrospectively.The Gensini scoring was used to assess the severity of coronary artery disease.The data were divided into three groups： group A （mild，29 cases） had 0-30 points；Group B （moderate，23 cases） had 31-60 points，and group C （severe，59 cases） had >60 points.First，the related factors affecting coronary artery disease were analyzed by univariate analysis.On this basis，the risk factors and protective factors were determined by Logistic regression analysis.Finally，the predictive value was determined by ROC curve.ResultsUnivariate analysis showed that there was no significant difference in general data among the 3 groups （P>0.05），but there were significant differences in laboratory indicators such as albumin，uric acid，high density lipoprotein cholesterol （HDL-C） and MPVLR （P<0.05）.High MPVLR level was an independent risk factor for high Gensini integration （OR=1.115，95%CI 1.009-1.239，P=0.047），and HDL-C was a protective factor.ConclusionsIn patients with chronic kidney disease，high MPVLR is an independent risk factor for the severity of coronary artery disease，and has the application value in predicting the severity of coronary artery disease.